2019
DOI: 10.1149/2.0751913jes
|View full text |Cite
|
Sign up to set email alerts
|

Time-Efficient Reparameterization and Simulation of Manufacturing Impacts on Performance of Lithium-Ion-Batteries

Abstract: The high quality demands of batteries for electric vehicles require powerful tools for error detection in cell manufacturing. Furthermore, cell diagnostics is a serious challenge because performance limitations occur on atomic scale and as batteries are closed systems physical issues can hardly be detected only with the aid of experimental methods. Physico-chemical models enable to detect up to seven various mechanisms of limitations but experimental parameterization is extensive. Therefore, in this study a fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The corresponding references are noted as comments in the boxes; this is visualized by the small red triangle in the top right‐hand corner. [ 10–13,15,16,18–21,30–168 ]…”
Section: Resultsmentioning
confidence: 99%
“…The corresponding references are noted as comments in the boxes; this is visualized by the small red triangle in the top right‐hand corner. [ 10–13,15,16,18–21,30–168 ]…”
Section: Resultsmentioning
confidence: 99%
“…10 and 11 respectively. 31 As indicated in Eq. 12, the effective electrolyte diffusion coefficient is calculated by applying the Bruggeman factor.…”
Section: Methodsmentioning
confidence: 99%
“…The influence of calendering on the electrochemical performance was also investigated by Lenze et al [ 79 ] using a P2D physico‐chemical battery model, based on the work by Legrand et al [ 80 ] In a coupled multi‐level model approach, Schmidt et al [ 81 ] and Thomitzek et al [ 82 ] combined a P2D model for simulating the battery cell, with a process chain model in order to analyze process–structure–property relationships and analyze the influence of tolerances in the manufacturing process on the processing parameters. They demonstrated that uncertainties in the calendering performance produce broad porosity distributions and that mass loading and thickness deviations have the highest impact on cell performance.…”
Section: Modeling Simulation and Tomographymentioning
confidence: 99%